Pulmonary Physician Consultancy in Emergency Services in Turkiye (PuPCEST) - a cross-sectional multicenter study - Diken, Ozlem Ercen; Kaya, Serife; Aksoy, Hayriye Bektas; Ekici, Aydanur; Capraz, Aylin; Tabaru, Ali; Ozlu, Tevfik (Lippincott Williams & Wilkins, 2024)
Pulmonology is one of the branches that frequently receive consultation requests from the emergency department. Pulmonology consultation (PC) is requested from almost all clinical branches due to the diagnosis and treatment of any respiratory condition, preoperative evaluation, or postoperative pulmonary problems. The aim of our study was to describe the profile of the pulmonology consultations received from emergency departments in Turkiye. A total of 32 centers from Turkiye (the PuPCEST Study Group) were included to the study. The demographic, clinical, laboratory and radiological data of the consulted cases were examined. The final result of the consultation and the justification of the consultation by the consulting pulmonologist were recorded. We identified 1712 patients, 64% of which applied to the emergency department by themselves and 41.4% were women. Eighty-five percent of the patients had a previously diagnosed disease. Dyspnea was the reason for consultation in 34.7% of the cases. The leading radiological finding was consolidation (13%). Exacerbation of preexisting lung disease was present in 39% of patients. The most commonly established diagnoses by pulmonologists were chronic obstructive pulmonary disease (19%) and pneumonia (12%). While 35% of the patients were discharged, 35% were interned into the chest diseases ward. The majority of patients were hospitalized and treated conservatively. It may be suggested that most of the applications would be evaluated in the pulmonology outpatient clinic which may result in a decrease in emergency department visits/consultations. Thus, improvements in the reorganization of the pulmonology outpatient clinics and follow-up visits may positively contribute emergency admission rates.
Keywords: emergency department; pulmonology; pulmonology consultation